Anabolic, Androgenic and Anti-Cholesterolemic Effect of Kigelia africana Leaf Extract on Some Male Wistar Rats - K, Dasofunjo (African Journal of Biochemistry and Molecular Biology Research, 2024)
Male erectile dysfunction (ED) refers to incompetency in reaching and retaining adequate penile tumescence for sexual intercourse, possibly due to hormonal imbalance or its inverse relationship with age. Over 152 million men globally suffer from ED and by 2025; the number of affected individuals is anticipated to be around 322 million. In this research work, the effect of petroleum ether extract of Kigelia africana on lipid profile and reproductive hormones of Wistar rats was examined. The leaf of K,africana was collected, air-dried , pulverized and extracted using 1200ml of 70% petroleum ether for 72 hours. This was then concentrated and stored in a refrigerator at 4°C. Twenty-one (21) Wistar male rats were used for this research. The animals were acclimatized for seven (7) days. Treatment was carried out as follows: group 1 (normal control) received only the vehicle (Normal saline) orally, while groups 2 and 3 received an extract of (200 and 400 mg/kg b.wt/day respectively for 2 successive weeks. The rats were sacrificed and the blood was collected by cardiac puncture for the analysis of lipid profile and reproductive hormones. The result revealed that the extract produced a significant increase (p<0.05) in serum testosterone, follicle-stimulating hormone, luteinizing hormone, TAG and HDL but a significant (p<0.05) decrease in serum total–cholesterol and LDL respectively when compared with normal control. It was speculated that the extract may possess anabolic, androgenic and anti/ hypocholesterolaemic effect which might reduce the risk of predisposition to both cardiovascular and erectile dysfunctions possibly due the presence of phytoandrogens and phytonutrients like alkaloids and flavonoids.